10.1016/s0197-2510(06)70444-2 (CrossRef Listing of Deleted DOIs, 2000)
Objective The polygenic risk score (PRS) for individuals with genetic generalized epilepsy (GGE) quantifies the common risk variants in genes identified in genome-wide association studies. We hypothesized that the phenotype of GGE patients differs based on their GGE PRS. Methods We identified participants with highest (n = 59) versus lowest (n = 48) PRS from the GGE patients (n = 2256) recruited through the Epi25 Collaborative for comparison. Detailed clinical data were acquired retrospectively for the 59 high PRS and 48 low PRS individuals with GGE from the Epi25 database and from the contributing centers. For validation, we accessed a larger cohort (n = 1175) of patients with GGE included in the Epi25 Collaborative. Results This study found no difference in phenotypic features of patients between the high-PRS GGE and low-PRS GGE subgroups, including age at onset, family history, and specific GGE syndrome. However, more patients from the lowest compared to the highest PRS subgroup were pharmacoresistant (31.7% vs. 8.9%, p = .01). On validation in a larger cohort, the PRS did not differ in the group of pharmacoresistant compared to nonpharmacoresistant patients. Significance No meaningful association between PRS and age at onset, history of febrile seizures, pre-/perinatal complications, epilepsy syndromes, seizure types, co-occurrence of functional/dissociative (nonepileptic) seizures, psychiatric comorbidities, electroencephalographic/magnetic resonance imaging findings, or drug response could be demonstrated in this study of people with GGE.